Csűry Bálint, a debreceni egyetem tanára - Hoffmann, István (Gerundium, 2013)
BÁLINT CSŰRY, PROFESSOR OF THE UNIVERSITY OF DEBRECEN. As professor of Hungarian and Finno-Ugrian linguistics, Bálint Csűry taught at the University of Debrecen from 1932 to 1941. In the course of these few years he made Debrecen the Carpathian Basin center and emblematic scene of vernacular language research. With this he contributed to the realization of his most important scholarly objectives aimed at making vernacular language reseach assume a worthy place among the disciplines of Hungarian linguistics. It is due to his eforts that in 1938, for the irst time in this country, an Institute of Hungarian Vernacular Research was established at the University of Debrecen.